Kebijakan Aplikasi PErlindungan Hukum Terhadap Korban Tindak Pidana Lingkungan Hidup Sehubungan Kegiatan Korporasi - Yeni Widowaty (Jurnal Media Hukum, 2009)
This research aims investigating and describing the factors influencing the policy of legal protection implementation of the EC victims done by corporate